Analysis of Lighting Intensity and Visual Comfort of Workers at PT PLN (Persero) UID Jawa Timur - Rafi Bayuaji; Endang Dwiyanti (International Journal of Science and Environment (IJSE), 2026)
Lighting is an important factor in supporting visual comfort, eye health, and work productivity. This study aims to analyze the level of lighting intensity in workspaces at the Heritage Building of PT PLN (Persero) UID East Java and evaluate its compliance with applicable standards. This research used a quantitative descriptive method with direct measurements using a lux meter at five work areas, namely Distribution, Commerce, Planning, Finance, as well as Communication and General Affairs. The results showed that most workspaces had lighting intensity below the minimum standard of 300 lux based on Minister of Manpower Regulation No. 5 of 2018. Only the Finance Division met the standard with an average of 339 lux. Inadequate lighting conditions may cause visual fatigue, decreased concentration, and reduced work productivity. Therefore, improvements in the lighting system are needed through additional lamps, optimization of natural lighting, and regular lamp maintenance.